Transport of taurine by normal human blood platelets - Ahtee, Lisa (1974)
1 Because normal human blood platelets contain higher concentrations of taurine than any other amino acid, and have a platelet: plasma concentration gradient exceeding 400: 1, we isolated the cells in vitro and incubated them with radioactively labelled taurine in order to investigate the existence of a metabolically-dependent accumulation process. 2 Platelets incubated with taurine (1 to 100 nmol/ml) in autologous plasma or Krebs solution accumulated [(14)C]-taurine against the concentration gradient. 3 The transport process was saturable at high concentrations, showed a requirement for sodium ions, and was temperature-dependent. 4 The kinetics of transport fulfilled the criteria of Michaelis & Menten for saturable enzyme/substrate interactions, but the kinetic constants were influenced by the incubation medium. 5 The metabolic inhibitors 2,4-dinitrophenol and iodoacetic acid in combination inhibited taurine transport in Krebs solution, but stimulated transport in autologous plasma. The latter result suggested the involvement of a sodium-dependent ATPase in taurine transport. 6 We conclude that platelets actively transport taurine in vitro under experimental conditions closely resembling those likely to occur in vivo, and that this taurine transport process may be involved in the maintenance of the platelet: plasma concentration gradient.